Intraperitoneal Bupivacaine 0.25% versus intravenous Diclofenac on post-operative analgesia in the cesarean section under spinal anesthesia: A prospective randomized comparative study in a tertiary care hospital of India - Pragyanrani Panda; Imran Ahmed; Mitesh Kumar Sharma; Rajesh De (Asian Journal of Medical Sciences)
Background: Cesarean section (CS) is a common surgical procedure, often accompanied by significant post-operative pain, which can hinder recovery, bonding with the baby, and breastfeeding. Effective pain management is crucial to prevent complications such as chronic pain and depression. Intraperitoneal (IP) instillation of local anesthetics, such as Bupivacaine has shown promise in providing analgesia, while intravenous (IV) Diclofenac is a common alternative.